2014
DOI: 10.3801/iafss.fss.11-510
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on Jet-A pool fire at high altitude

Abstract: For the further assessment on cargo fire hazard, full-scale Jet-A pool fire tests under the specifications of FAA Minimum performance standard (MPS) were conducted in sea-level Hefei and high-altitude Lhasa. A square insulation board (1.2m×1.2m) was place upon the fuel pan to simulate the effect of ceiling on fire plume. The experimental results indicates that the mass burning rate is proportional to the 2/3 power of the ambient pressure, in accordance with the theoretical prediction for convection-dominant fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The parameters of 0.058 kg/m 2 s and 0.65 were obtained. This is close to the burning rate ratio of 0.74 that was obtained in the experiment by Zhou et al 32 where Jet-A aviation kerosene was used at Lhasa (3650 m, 65.2 kPa) and Hefei (20 m, 101 kPa). The decrease in burning rate will further affect parameters including air entrainment, flame shape, flame and smoke temperature, flame radiation and smoke density, making the combustion law of liquid fuel at high altitudes quite different to that at sea level.…”
Section: Burning Ratesupporting
confidence: 88%
See 1 more Smart Citation
“…The parameters of 0.058 kg/m 2 s and 0.65 were obtained. This is close to the burning rate ratio of 0.74 that was obtained in the experiment by Zhou et al 32 where Jet-A aviation kerosene was used at Lhasa (3650 m, 65.2 kPa) and Hefei (20 m, 101 kPa). The decrease in burning rate will further affect parameters including air entrainment, flame shape, flame and smoke temperature, flame radiation and smoke density, making the combustion law of liquid fuel at high altitudes quite different to that at sea level.…”
Section: Burning Ratesupporting
confidence: 88%
“…The fitting index of the radiation model is 0.587. Small‐scale oil pools were used in the previous oil pool fire experiment in a low‐pressure environment 32,34,35 . These small‐scale oil pool fire experiments produced less smoke and uncontrolled thermal radiation combustion.…”
Section: Resultsmentioning
confidence: 99%
“…The actual burning rate during a pool fire varies; thus, researchers usually choose a relative steady state that is close to the peak burning rate, called the quasi-steady stage, in pool fire studies. 3335 Therefore, the quasi-steady stage in our study is shown in Figure 8. The averaged actual burning rates with an error of 2%–5% at the quasi-steady stage in all cases are also shown in Figure 8, and the transformed burning rate data m · is also listed in Table 4.…”
Section: Resultsmentioning
confidence: 77%